2014
DOI: 10.2147/ndt.s59375
|View full text |Cite
|
Sign up to set email alerts
|

Influence of valproate on the required dose of propofol for anesthesia during electroconvulsive therapy of bipolar affective disorder patients

Abstract: BackgroundPropofol is often used as an anesthetic agent for electroconvulsive therapy (ECT). In recent studies, propofol was shown to possess significant seizure-shortening properties during ECT. “Valproate” is a mood stabilizer used mainly in the treatment of bipolar affective disorder. It is reported that valproate, being an anticonvulsant, raises the seizure threshold, thus decreases the efficacy of ECT treatment.AimThe purpose of our study was to compare the dose of propofol in valproate-using patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Some studies have indicated that relationships exist between anticonvulsant use and the required propofol dose or the emergence time from propofol‐induced anaesthesia. Two previous studies have investigated the clinical influence of valproate on the dose of propofol required to induce anaesthesia (Ishii et al ., ; Hizli Sayar et al ., ). These studies demonstrated that valproate reduced the dose of propofol required to induce anaesthesia.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have indicated that relationships exist between anticonvulsant use and the required propofol dose or the emergence time from propofol‐induced anaesthesia. Two previous studies have investigated the clinical influence of valproate on the dose of propofol required to induce anaesthesia (Ishii et al ., ; Hizli Sayar et al ., ). These studies demonstrated that valproate reduced the dose of propofol required to induce anaesthesia.…”
Section: Discussionmentioning
confidence: 97%
“…A clear limitation of this assessment is the assumption that the clinical efficacy of ECT depends solely on the electrical length of the evoked seizure, when there is no evidence that this assumption is true ( Fear et al, 1994 ; Geretsegger et al, 1998 ; Sackeim, 1999 ; Azuma et al, 2007 ; Bauer et al, 2009 ; Stewart, 2012 ; Martinez-Amoros et al, 2014 ). In fact, different values for the lower limit of the electrical convulsion can be found in the literature: 15 s ( Gonzalez et al, 2007 ), 20 s ( Bertolin-Guillen et al, 2006 ; Ramirez-Segura and Ruiz-Chow, 2013 ), 25 s ( Nguyen et al, 1997 ; Dogan et al, 2011 ; Gombar et al, 2011 ; Hizli Sayar et al, 2014 ; Martinez-Amoros et al, 2014 ), and 26 s ( Wang et al, 2011 ). These data preclude us from directly comparing the percentage of sessions that were considered ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing exposure to psychoactive agents utilized for sedation may be considered, especially as respiratory mechanics improve. Administration of agents that have been used in critical care for agitation, such as valproate, may reduce concomitant psychoactive medication use, although further investigation is required 95, 96 …”
Section: Miscellaneousmentioning
confidence: 99%